2020
DOI: 10.30773/pi.2020.0118
|View full text |Cite
|
Sign up to set email alerts
|

Personality Beliefs in Obsessive-Compulsive Disorder: How Are They Related to Symptom Severity?

Abstract: Objective The comorbidity of obsessive-compulsive disorder (OCD) and personality disorders (PDs) is frequent but there are conflicting findings about which PDs are the most common. This study aimed to investigate the personality beliefs that exist on a more pathological level among OCD patients, to explore the association between personality beliefs and OCD severity, and to clarify the mediator effect of depression in this relationship.Methods 202 OCD patients and 76 healthy controls with similar sociodemograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Previous research showed that avoidant personality beliefs were significantly higher in the OCD group than healthy individuals. However, no research about avoidant personality beliefs found in the danger/checking subtype ( 8 ). The results of the BEI showed that obsessive perfection beliefs and obsessive personality beliefs were the links between obsessive beliefs and personality beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research showed that avoidant personality beliefs were significantly higher in the OCD group than healthy individuals. However, no research about avoidant personality beliefs found in the danger/checking subtype ( 8 ). The results of the BEI showed that obsessive perfection beliefs and obsessive personality beliefs were the links between obsessive beliefs and personality beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…These cognitive characteristics are said to be the main point of emphasis and the change process in cognitive therapies for personality disorders ( 7 ). The results showed that histrionic, borderline, dependent, avoidant, and paranoid personality beliefs were significantly more elevated in the PwOCD compared to healthy individuals ( 8 ). The broad definition of OCD in the DSM-5, however, considers that the symptoms result from a specific and unique compulsive behavior and defects in the behavioral inhibition dimension ( 6 ).…”
mentioning
confidence: 89%